Pendampingan Digital Marketing Untuk Umkm Rengginang Udang di Kelurahan Yosodadi Kecamatan Metro Timur - Iswati Iswati; Heri Cahyono; Cahaya Khaeroni; Kuliyatun Kuliyatun; Wulan Nur Azizah; Faizah Kanti; Atiq Kundaratul; Fatiya Asri; Annisa’ul Insyirah (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
The food and beverage business in Indonesia, especially the snack business, has developed very rapidly, players in this sector are not only dominated by old players who have great reputations in the Indonesian food and beverage industry, but are also surrounded by new players, imported products. , even now snacks produced by home industries or what are known as small and medium unit products (SMEs), have been distributed to the modern market, which is making this sector increasingly busy and congested. One of the traditional snacks available and consumed by Indonesian people is Rengginang. Rengginang is a snack usually made from sticky rice. Rengginang Udang is one of the processed snack products in Rw 06, Yosodadi Village, East Metro District, which was founded in 2020. Marketing management really needs to be understood by companies, so that they can take advantage of market opportunities by applying production concepts, product concepts, sales concepts, marketing concept, and social-oriented marketing concept. What needs to be done is to carry out a marketing strategy analysis which can be done through appropriate digital marketing to overcome these problems using various stages and analytical tools in the marketing strategy. It is hoped that the results of this marketing strategy analysis will be able to determine the right marketing strategy for entrepreneurs so that they can continue to survive and develop an appropriate competitive strategy to face all possible changes that occur in the business environment. Through digital marketing strategies, you can also create or open new markets that were previously closed due to limited time, communication methods or distance.